Amniotic membrane is a potential regenerative option for chronic non‐healing wounds: a report of five cases receiving dehydrated human amnion/chorion membrane allograft. Issue 4 (14th May 2015) - Mrugala, Andrew; Sui, Audrey; Plummer, Malgorzata; Altman, Igor; Papineau, Elaine; Frandsen, Devn; Hill, Danielle; Ennis, William J
Abstract: A case series of five patients with a total of six chronic non‐healing wounds (>30 day duration) were non‐randomly selected to evaluate the performance, safety and handling properties of dehydrated human amnion/chorion membrane allograft, an amniotic membrane scaffolding product. The patients had lower extremity wounds that had previously failed standard of care within a university outpatient/inpatient wound healing programme. Five wounds treated with dehydrated amnion/chorion membrane allograft showed a mean 43% area reduction from baseline (51% median) at 3 weeks into treatment and completely healed with a 64‐day median time to closure (SD ±27·6 days). One wound worsened at 3 weeks and was found to have a complete central vein obstruction that was treated with long‐term mild compression but still eventually healed at 6 months. Removing this outlier, the four responding wounds had a 72% mean and 69% median change in area from baseline, at the 3 week point. All five patients received only one application of dehydrated human amnion/chorion membrane allograft, and there were no adverse events. The product was easy to use, administer and handle. In summary, dehydrated human amnion/chorion membrane allograft appears to be a safe, effective and easy to use therapy for chronic non‐healing wounds. This study describes the details of these clinical cases and provides an overview of the current evidence on the use of amniotic tissue in clinical practice.